Investigasi Faktor yang Mempengaruhi Kepuasan Pengunjung Museum Tsunami Aceh - Nurfajrina Nurfajrina; Cut Aprilia (Jurnal Administrasi Bisnis, 2022)
Aceh Tsunami Museum is one of Aceh tourism attractions that has gained recognition nationally and globally. Since 2011 until 2018, the museum only experienced one dropped in the number of visitors which reflects its popularity as tourism destination. This study aims to investigate the effect of Authenticity, Involvement, and Destination Image toward visitor satisfaction of Aceh Tsunami Museum. The sample used in this study were 159 Aceh Tsunami Museum visitors. Data collection was carried out using a questionnaire. Hierarchical Linear Modeling (HLM) is used as a method of analysis to determine the effect of all the variables involved. (1) The results of this study found that Authenticity and Involvement have a positive effect on satisfaction and Destination Image; (2) This study also found that destination image partially mediates the relationship between Authenticity and Satisfaction as well as the relationship between Involvement and Satisfaction; (3) In addition, this study found a direct influence between Destination Image and Satisfaction.